2015
DOI: 10.1128/aem.03726-14
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Cutworm Larvae Is Not Enhanced by Agrotis segetum Granulovirus and Agrotis segetum Nucleopolyhedrovirus B Coinfection Relative to Single Infection by Either Virus

Abstract: Mixed infections of insect larvae with different baculoviruses are occasionally found. They are of interest from an evolutionary as well as from a practical point of view when baculoviruses are applied as biocontrol agents. Here, we report mixed-infection studies of neonate larvae of the common cutworm, Agrotis segetum, with two baculoviruses, Agrotis segetum nucleopolyhedrovirus B (AgseNPV-B) and Agrotis segetum granulovirus (AgseGV). By applying quantitative PCR (qPCR) analysis, coinfections of individual la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…This group includes NPVs (six group 2-and one group 1-alphabaculoviruses) and GVs from Agrotis segetum [10,44], Helicoverpa armigera [45,46], Mythimna unipuncta [47,48], S. frugiperda [49,50], S. litura [32,51], Trichoplusia ni [52,53], and Choristoneura fumiferana [54]. All these GVs are of the slowly killing type and a potentiating effect has only been reported to NPVs for S. frugiperda [13,55,56]. Probably, coinfection with NPVs is an evolutionary strategy selected in some slowly killing GVs to persist and spread in nature.…”
Section: Discussionmentioning
confidence: 99%
“…This group includes NPVs (six group 2-and one group 1-alphabaculoviruses) and GVs from Agrotis segetum [10,44], Helicoverpa armigera [45,46], Mythimna unipuncta [47,48], S. frugiperda [49,50], S. litura [32,51], Trichoplusia ni [52,53], and Choristoneura fumiferana [54]. All these GVs are of the slowly killing type and a potentiating effect has only been reported to NPVs for S. frugiperda [13,55,56]. Probably, coinfection with NPVs is an evolutionary strategy selected in some slowly killing GVs to persist and spread in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Hackett et al (2000) found that a GV isolated from H. armigera inhibited the replication of HearNPV in H. zea larvae. Independent action was also reported: neither an increase nor a decrease in mortality was observed in mixed-virus treatments of Agrotis segetum larvae with Agrotis segetum granulovirus and Agrotis segetum nucleopolyhedrovirus B (Wennmann et al 2015). Concerning NPVs-NPVs interactions in vivo, studies focused on different strains (wild-type and/or genetically modified) of the same NPV species (Georgievska et al 2010, Virto et al 2014.…”
Section: Speed Of Kill Of Acmnpv and Ranunpv In R Nu Larvae Following...mentioning
confidence: 99%
“…To determine ODV fusion, RFUs was measured again as described. Fifty µL of labeled ODV of CpGV-M or CpGV-S were measured as a positive control to calculate the total amount of ODV (for details see [41]). Measured RFUs were corrected for background fluorescence associated with the midgut epithelial cells from control larvae fed with water.…”
Section: Odv and Fluorescence Dequenching Assaymentioning
confidence: 99%